Opportunity Unraveled: Private Information and the Missing Markets for Financing Human Capital - Herbst, Daniel; Hendren, Nathaniel (American Economic Review, 2024)
We examine whether adverse selection has unraveled private markets for equity and state-contingent debt contracts for financing higher education. Using survey data on beliefs, we show a typical college-goer would have to repay $1.64 in present value for every $1 of financing to overcome adverse selection in an equity market. We find that risk-averse college-goers are not willing to accept these terms, so markets unravel. We discuss why moral hazard, biased beliefs, and outside credit options are less likely to explain the absence of these markets. We quantify the welfare gains for subsidizing equity-like contracts that mitigate college-going risks. (JEL D82, D83, G51, I22, I23, I26, J24)